The Effectiveness of Reminiscence Therapy on Alleviating Depressive Symptoms in Older Adults: A Systematic Review - Liu, Zhuo; Yang, Fan; Lou, Yifan; Zhou, Wei; Tong, Feng (Frontiers in Psychology, 2021)
Objective: Depression is one of the most common problems faced by older adults. Reminiscence therapy, defined as using the recall of past events, feelings, and thoughts facilitating pleasure, is one type of psychotherapy that could alleviate depressive feelings among older adults, improve their quality of life, and help them live independently. Reminiscence therapy originated from geriatric psychiatry, and is an effective non-pharmacological intervention that could be structured or unstructured and be conducted individually or in a group. The current systematic review was designed to summarize and review existing evidence on the effect of reminiscence therapy on depression in older adults. Methods: We conducted a systematic review from January 2000 to Mar 2021 using ten electronic databases in English and Chinese languages, including Medline, Embase, Cinahl, PsychInfo, Cochrane, Web of Science, Google Scholar, Science Direct, CNKI, and Wanfang. We excluded studies that didn’t use randomized controlled trials (RCT) from the meta-analysis. The selected studies were scored using the Cochrane Risk of Bias tool. The RevMan 5.0 was used in subgroup analysis depending on how the interventions were classified. Results: We extracted 527 studies based on keyword searches, of which 10 RCTs met inclusion criteria were included in the meta-analysis. The meta-analysis yielded high heterogeneity, and the analyses of significant subgroups showed that reminiscence therapy has a significant effect on relieving depressive symptoms in older adults. Reminiscence therapy benefits older adults with chronic illness and those on antidepressants as well. The effect and cost-effectiveness of group reminiscence therapy were higher than individual reminiscence therapy. And some specific types of group reminiscence therapy have a significant effect on improving depression and secondary outcomes, including life satisfaction. Although the effectiveness of structured and unstructured group reminiscence on depression has no significant differences according to current evidence, the structured therapy is more replicable, generalizable, and user-friendly due to its detailed protocol for new therapists. Furthermore, reminiscence therapy is more effective for older women and older adults with more severe depressive symptoms. Conclusion: The evidence-based protocol and implementation of reminiscence interventions need to be further developed and standardized to facilitate global use.